Awareness and Use of Internet Based E-Information Resources among School Children: A Case Study of Bijapur District, Karnataka - Kulkarni, Deepa R.; Tadasad, P. G. (Journal of Information and Knowledge, 2015)
The present study investigates the awareness and use of internet based e-information resources among school children in two selected schools of Bijapur of Karnataka State. Based on a survey of 120 students, the study emphasizes the awareness and use of e-information sources. It assesses and analyzes the acquaintance of school children with IT, awareness and use of internet, problems encountered awareness about searching e-information sources, types of sources preferred, reasons for not using e-information sources, channels preferred, and ability of them to use e-information sources.